2014
DOI: 10.1108/afr-10-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Default risk in agricultural lending, the effects of commodity price volatility and climate

Abstract: Purpose -Commodity price volatility and small variations in climate conditions may have an important impact on the creditworthiness of any agricultural project. The evolution of such risk factors is vital for the credit risk analysis of a rural bank. The purpose of this paper is to determine the importance of price volatility and climate factors within a default risk model. Design/methodology/approach -The authors estimate a generalized linear model (GLM) based on a structural default risk model. With the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
(41 reference statements)
3
16
0
Order By: Relevance
“…However, the effect of temperature seems to be very modest. This result is consistent with the work of Castro and Garcia (2014), in that warmth and rainfall contribute to agricultural production as long as they do not surpass certain thresholds. The Year dummies have an effect on default; however, in this paper, the main idea is for them to absorb macroeconomic factors that are not included in our control variables.…”
Section: Agriculture-related Loans and Credit Risksupporting
confidence: 92%
See 1 more Smart Citation
“…However, the effect of temperature seems to be very modest. This result is consistent with the work of Castro and Garcia (2014), in that warmth and rainfall contribute to agricultural production as long as they do not surpass certain thresholds. The Year dummies have an effect on default; however, in this paper, the main idea is for them to absorb macroeconomic factors that are not included in our control variables.…”
Section: Agriculture-related Loans and Credit Risksupporting
confidence: 92%
“…Weber and Musshoff's (2012) results suggest that, in the Tanzanian loan market, agricultural firms have lower delinquency rates than non-agricultural firms do. Castro and Garcia (2014) and Ouyang and Zhang (2019) find that commodity price volatility and climate factors have a modest impact on agricultural loans, while macroeconomic conditions for the agricultural sector and intermediate input prices have greater influence. Dinterman et al (2018) study how economic factors have impacted farm businesses in the United States.…”
Section: B Role Of Collateralmentioning
confidence: 99%
“…Furthermore, de Nicola (2015) found that climatic factors explain variation in loan default. In addition, Castro and Garcia (2014) also found a significant effect of climatic factors on default of agricultural loans. In summary, even though farmers show a good repayment performance, the direct dependence of production on external weather factors leads to the perception that agriculture is riskier than other business.…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…In summary, weather patterns can be linked to agricultural loan default, and extreme weather events are likely to increase the rate of default. Castro and Garcia (2014) emphasized the need of banks to manage common risks to agriculture through quantitative risk management. Dercon (2004) showed that the economic impact of a rainfall shock is long-lasting.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Various quantitative approaches can be used to evaluate the safety and soundness of lending institutions (Castro and Garcia, 2014). Lending institutions source capital from various entities and provide capital to borrowers.…”
Section: Capital Adequacymentioning
confidence: 99%